Оптичні сенсори фізичних та хімічних величин на базі напівпровідникових наноматеріалів - Сушко, О. А.; Білаш, О. М.; Рожицький, М. М. (ХНУРЕ, 2013)
In abstract a development of a portable optical sensor based on semiconductor quantum dots (QD) is considered. QDs are used as the detector elements of nanophotonic sensor for analyte detection in the environmental objects. The principle of nanophotonic sensor operation is based on electrochemical and electrochemiluminescence methods using modern nanomaterials and nanotechnologies. The operation of nanophotonic sensor is based on a process of QDs transfer to ionic forms in a consequence of electrochemical processes, subsequent reactions with oppositely charged ionic forms of the analyte, resulting in the emission of an analytical optical signal. The number of quanta emitted at the given period of time is a measure of analyte content. Optical sensor with nanomaterials as detector elements has such advantages as assay reproducibility, low limit of detection, cheapness of construction and versatility. It can be used in ecology for investigation and monitoring of water object for dangerous carcinogenic substances content detection.
Keywords: Сенсор; сферичні квантово-розмірні структури; технологія Лангмюра-Блоджетт; електрохемілюмінесценція